2016
DOI: 10.1186/s13047-016-0149-2
|View full text |Cite
|
Sign up to set email alerts
|

If the shoe fits: development of an on‐line tool to aid practitioner/patient discussions about ‘healthy footwear’

Abstract: BackgroundA previous study highlighted the importance of footwear to individuals’ sense of their identity, demonstrating that shoes must ‘fit’ someone socially, as well as functionally. However, unhealthy shoes can have a detrimental effect on both foot health and mobility. This project utilises qualitative social science methods to enable podiatrists to understand the broader contribution of footwear to patients’ sense of themselves and from this an online toolkit was developed to aid footwear education.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…Of our sample, 57% reported that they had received foot care advice; yet, fewer than 50% of our respondents reported that they were confident in knowing how to manage their children's feet problems. Health education and access to specialist foot care services are clearly important, and this study adds to existing concerns about footwear (Farndon, Robinson, Nicholls, & Vernon, ) and highlights the need for carefully directed education which involves parents/parental caregivers and their children. Given the health burden faced by this population, it is important that children have access to health professionals that understand the complex pathways to the types of foot problems reported in this study.…”
Section: Discussionmentioning
confidence: 67%
“…Of our sample, 57% reported that they had received foot care advice; yet, fewer than 50% of our respondents reported that they were confident in knowing how to manage their children's feet problems. Health education and access to specialist foot care services are clearly important, and this study adds to existing concerns about footwear (Farndon, Robinson, Nicholls, & Vernon, ) and highlights the need for carefully directed education which involves parents/parental caregivers and their children. Given the health burden faced by this population, it is important that children have access to health professionals that understand the complex pathways to the types of foot problems reported in this study.…”
Section: Discussionmentioning
confidence: 67%
“…More recently, research with patients and podiatrists explores why patients may resist practitioner advice around changing their footwear practices and draws more explicitly on social science theories and methodologies, bringing together a research team of podiatrists and social scientists [ 27 ]. Building directly on a previous sociological research project in this area [ 11 ] which received a high level of interest from podiatrists, semi-structured interviews and focus groups were utilised alongside more innovative methods such as photography and shoe diaries in order to explore patients’ relationships with shoes and real or perceived barriers to adopting ‘healthier’ footwear.…”
Section: Widening Understandings Of ‘Fit’: Social Science In Healthcamentioning
confidence: 99%
“…Whilst the increasing recognition of the links between footwear and identity is of course welcome, it is essential that the findings of such work are fed back into podiatrist training and practice that recognises that patient values, motivations and practices in relation to the embodied experiences of choosing and wearing shoes are complex. Recent research in this field [ 27 ] has led to the development of an online toolkit, recommendations for practice and a visual tool, all designed to directly inform practice in patient consultations and to encourage practitioners to reconceptualise fit more broadly and find ways to discuss this wider understanding of fit with their patients. Although there is further research to be done to consider how developments such as the toolkit can more directly inform training and practice, the findings of a range of previous research suggest that tools such as Motivational Interviewing (MI) are likely to be of value in clinical settings [ 30 ].…”
Section: Implications For Practicementioning
confidence: 99%
“…Footwear advice in a clinical setting is often incorporated into effective treatment plans when ill-fitting shoes are linked to the presenting complaint, yet there is little understanding as to what specific advice should be given. Although, some footwear assessment tools are available to guide clinicians on evaluating shoes [9,10], there are factors that categorise "healthy" footwear that are ill founded and often based on myth. Additionally, it should be noted that when assessing footwear, the shoes worn to clinic appointments are often picked for convivence rather than a true representation of what is regularly worn [6].…”
Section: Introductionmentioning
confidence: 99%